Order Invariant Tests for Proper Calibration of Multivariate Density Forecasts - Jonas Dovern; Hans Manner (Center for Economic Studies and ifo Institute (CESifo), 2018)
Established tests for proper calibration of multivariate density forecasts based on Rosenblatt probability integral transforms can be manipulated by changing the order of variables in the forecasting model. We derive order invariant tests. The new tests are applicable to densities of arbitrary dimensions and can deal with parameter estimation uncertainty and dynamic misspecification. Monte Carlo simulations show that they often have superior power relative to established approaches. We use the tests to evaluate GARCH-based multivariate density forecasts for a vector of stock market returns.
Keywords: C12; C32; C52; C53; 330; density calibration; goodness-of-fit test; predictive density; Rosenblatt transformation